2017
DOI: 10.1016/j.neuron.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Locked Inhibition, but Not Excitation, Underlies Hippocampal Ripple Oscillations in Awake Mice In Vivo

Abstract: SummarySharp wave-ripple (SWR) oscillations play a key role in memory consolidation during non-rapid eye movement sleep, immobility, and consummatory behavior. However, whether temporally modulated synaptic excitation or inhibition underlies the ripples is controversial. To address this question, we performed simultaneous recordings of excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) and local field potentials (LFPs) in the CA1 region of awake mice in vivo. During SWRs, inhibition dominated ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
106
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 28 publications
18
106
0
Order By: Relevance
“…Thus, KCC2 knockdown in cortical PCs was shown to also profoundly perturb neuronal excitability as well as network activity (Kelley et al , 2018; Goutierre et al , 2019). Since PV INs exert a critical control over the activity of cortical PCs (Pouille & Scanziani, 2001) and shape their rhythmic activities (Klausberger & Somogyi, 2008; Amilhon et al , 2015; Gan et al , 2017), altered CCC expression in these cells would be expected to profoundly perturb cortical rhythmogenesis. As most studies on CCC expression in the pathology lacked cell-subtype resolution, whether and how it is affected in PV INs remains to be fully explored and the consequences on cortical activity should then be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, KCC2 knockdown in cortical PCs was shown to also profoundly perturb neuronal excitability as well as network activity (Kelley et al , 2018; Goutierre et al , 2019). Since PV INs exert a critical control over the activity of cortical PCs (Pouille & Scanziani, 2001) and shape their rhythmic activities (Klausberger & Somogyi, 2008; Amilhon et al , 2015; Gan et al , 2017), altered CCC expression in these cells would be expected to profoundly perturb cortical rhythmogenesis. As most studies on CCC expression in the pathology lacked cell-subtype resolution, whether and how it is affected in PV INs remains to be fully explored and the consequences on cortical activity should then be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, parvalbumin-expressing interneurons (PV INs), which receive excitatory inputs from both local and distant PCs, in turn provide them with fast perisomatic inhibition (Hu et al , 2014). Fast inhibitory signaling by PV INs controls the timing of principal cell activity (Pouille & Scanziani, 2001) and plays a major role in the generation of rhythmic activities (Klausberger & Somogyi, 2008; Amilhon et al , 2015; Gan et al , 2017) as well as the segregation of PCs into functional assemblies (Agetsuma et al , 2018). However, in addition to excitatory inputs from PCs, PV INs also receive GABAergic innervation from local interneurons (Chamberland & Topolnik, 2012), including some specialized in interneuron inhibition (Gulyas et al , 1996), as well as long-range projecting interneurons (Freund & Antal, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The biophysical model of CA3-CA1 SWR activity which we propose in this study builds on an extensive literature on the mechanisms of ripples and sharp waves. In vitro and in vivo studies have shown that in CA1 ripples are dominated by inhibitory phasic activity (Gan et al 2017; Schlingloff et al 2014), and basket cells spike at high frequency (Schlingloff et al 2014; Varga et al 2012) in localized groups (Patel et al 2013). Meanwhile, pyramidal cells spike relatively rarely, phase-locked to windows of opportunity left by the ongoing oscillatory inhibitory signal (Csicsvari et al 1999a; b).…”
Section: Discussionmentioning
confidence: 99%
“…Balanced excitation–inhibition (E/I) during activity is a common feature of neuronal networks (Anderson, Carandini, & Ferster, ; Haider, Duque, Hasenstaub, & McCormick, ; Okun & Lampl, ; Rudolph, Pospischil, Timofeev, & Destexhe, ). During evoked activity and local field potential (LFP) oscillations, balanced E/I currents underlie depolarizations in hippocampal and cortical excitatory principal cells in vivo (Atallah & Scanziani, ; Gan, Weng, Pernía‐Andrade, Csicsvari, & Jonas, ; Wilent & Contreras, ). A key characteristic of balanced E/I inputs is that they maintain membrane voltage near spike threshold and permit precise control over spike output rate (Gabernet, Jadhav, Feldman, Carandini, & Scanziani, ; Higley & Contreras, ; Shu, Hasenstaub, & McCormick, ; Wehr & Zador, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recruitment of inhibition over a range of network activity levels likely prevents runaway excitation in networks with strong recurrent connections such as the subiculum (Drexel et al, ; Harris, Witter, Weinstein, & Stewart, ). In the hippocampus, fast frequency oscillations such as gamma (30–80 Hz) and ripples (~200 Hz) have been shown to have properties consistent with generation through correlated and balanced synaptic currents (Atallah & Scanziani, ; English et al, ; Gan et al, ). For lower frequencies such as theta (3–12 Hz), however, balanced network activity has not been recognized as a potentially contributing factor to this oscillation range.…”
Section: Introductionmentioning
confidence: 99%